SYNECTIC MODEL INCREASES SELF CONFIDENCE OF EARLY CHILDHOOD - Yuliani Safitri; Heni Komalasari (Universitas Pendidikan Indonesia, 2024)
This study focuses on Self Confidence or self-confidence of early childhood in dance learning. Low self-confidence of early childhood because they are not given the opportunity to explore in learning and make children feel bored and the learning and teaching atmosphere is not fun. This learning process aims to foster self-confidence or self-confidence of children and change their behavior to be more creative and active in learning. The method used in this study is quantitative using experiments where this study observes and observes phenomena by collecting data that can be measured using statistics. Data collection used in this study is interviews and also documentation of learning outcomes. The results of the study showed that self-confidence or self-confidence of children increased by 28% after the application of the synectic model in dance learning. Ideally, the self-confidence possessed by individuals must be in the very high category. This is intended to be able to develop aspects that exist within themselves, high self-confidence is needed in the individual. The aspects that need to be possessed are confidence, optimism, independence, responsibility, and rationality. The Synectic approach model in increasing children's self-confidence has a great influence on the results and creates an active, fun, and non-boring learning atmosphere. This is an approach used to foster creative and active thinking from a group of children who learn and play together.